NON-COMMUNICABLE DISEASES (NCDs) CHOLESTEROL THROUGH POINT OF CARE TESTING (POCT) IN LABUAN BAJO VILLAGE, BANAWA DISTRICT, DONGGALA REGENCY - Tiara Agustina; Siti Nurhaliza Hinelo; Vadyan Raehandy Thufeil; Nursabita Chaerani; Yescika Tricia Torae; Yuyun Dinda Sauru; Zahwa Radilva; Nurfadila; Shinta Nugraini; Kholid Mu'tasim; Revalina Febriani A. Hasan; Salsabila (PT. Radja Intercontinental Publishing, 2026)
Hypercholesterolemia is a pathological condition characterized by excessive accumulation of cholesterol in the blood that can trigger serious cardiovascular complications, including coronary heart disease and stroke. This study aims to describe the distribution of total cholesterol levels and the level of community knowledge regarding non-communicable diseases (NCDs) in Labuan Bajo Village through the Point of Care Testing (POCT) method. A descriptive survey method with a qualitative approach was employed, involving 17 respondents from RT 01 and RT 02, Labuan Bajo Village, Banawa District, Donggala Regency, on January 15, 2026. Capillary blood samples were examined using the NESCO Multicheck N-01 device. Results revealed that 41.2% of respondents had high cholesterol levels (≥240 mg/dL), 23.5% were at borderline high (200-239 mg/dL), and 35.3% had normal levels (<200 mg/dL). Furthermore, 82.3% of respondents demonstrated low to very low knowledge about hypercholesterolemia. Key contributing factors include advanced age, high-fat dietary habits of coastal communities, and limited access to health information. POCT proved effective and efficient as a community-based early detection instrument for non-communicable diseases.